Impaired Fetal Environment and Gestational Age: What Is Driving Mortality in Neonates With Critical Congenital Heart Disease?. Issue 22 (19th November 2019) - Steurer, Martina A.; Peyvandi, Shabnam; Baer, Rebecca J.; Oltman, Scott P.; Chambers, Christina D.; Norton, Mary E.; Ryckman, Kelli K.; Moon‐Grady, Anita J.; Keller, Roberta L.; Shiboski, Stephen C.; Jelliffe‐Pawlowski, Laura L.
Abstract : Background: Infants with critical congenital heart disease (CCHD) are more likely to be small for gestational age (SGA) or born to mothers with maternal placental syndrome. The objective of this study was to investigate the relationship between maternal placental syndrome, SGA, and gestational age (GA) on 1‐year mortality in infants with CCHD. Methods and Results: In a population‐based administrative database of all live‐born infants in California (2007–2012) we identified all infants with CCHD without chromosomal anomalies. Our primary predictor was an impaired fetal environment (IFE), defined as presence of maternal placental syndrome or SGA. We calculated hazard ratios to quantify the association between different components of IFE and 1‐year mortality and conducted a causal mediation analysis to assess GA at birth as a mediator. We identified 6863 infants with CCHD. IFE was present in 25.1%. Infants with IFE were more likely to die than infants without IFE (16.6% versus 11.1%; hazard ratios 1.55, 95% CI 1.34–1.78). Only SGA (hazard ratios 1.76, 95% CI 1.50–2.05) and placental abruption (hazard ratios 1.70, 95% CI 1.17–2.48) were significantly associated with mortality; preeclampsia and gestational hypertension had no significant association with mortality. The mediation analysis showed that 32.8% (95% CI 24.9–47.0%) of the relationship between IFE and mortality is mediated through GA. Conclusions: IFE is a significant contributor to outcomes in the CCHD population. SGA and placental abruption are the main drivers of postnatal mortality while other maternal placental syndrome components had much less of an impact. Only one third of the effect between IFE and mortality is mediated through GA.